Sign Language Studies with Chimpanzees in Sanctuary - Mary Lee Jensvold; Kailie Dombrausky; Emily Collins (Animals, 2023)
Adult chimpanzees Tatu and Loulis lived at the Fauna Foundation sanctuary. They had acquired signs of American Sign Language (ASL) while young and continued to use them as adults. Caregivers with proficiency in ASL maintained daily sign language records during interactions and passive observation. Sign checklists were records of daily vocabulary use. Sign logs were records of signed interactions with caregivers and other chimpanzees. This study reports sign use from eight years of these records. Tatu and Loulis used a majority of their base vocabularies consistently over the study period. They used signs that they had acquired decades earlier and new signs. Their utterances served a variety of communicative functions, including responses, conversational devices, requests, and descriptions. They signed to caregivers, other chimpanzees, including those who did not use signs, and to themselves privately. This indicates the importance of a stimulating and interactive environment to understand the scope of ape communication and, in particular, their use of sign language.